Analysis of employee recruitment in supporting performance in the Gipang Singo Mas company - Wulandari, Efriza Pahlevi; Ariska, Aas; Indrasari, Melinda; Giovanni, Adam (NUsantara Islamic Economic Journal, 2024)
Recruitment is the company’s first step to get employees who are competent and can make a good contribution to the company. This study aims to find out how the role of employee recruitment is supporting performance at the Gipang Singo Mas company. The research is a qualitative research, by using data collection techniques in the form of interviews, documentation, and literature study. Literature study is a series of activities related to methods of collecting library data, reading and recording, and processing research materials. The sample in this 1 company owner and 4 employees. The results of this study indicate that the Singo Mas braid company uses closed methods in its recruitment activities. Where there are parties who recommend an employee to work in this company. Most of them, these employees are factory employees who have resigned from their jobs. With that, it will make it easier for companies to conduct training, because the employees who enter already have work experience. The role of recruitment greatly affects the company’s performance, where the better the employees produced and this has a significant on company performance